FACTORS AFFECTING AUDIT DELAY (STUDY OF MANUFACTURING COMPANIES LISTED ON MALAYSIAN STOCK EXCHANGE FOR THE 2019-2022 PERIOD) - Icih; Norhanizah Johari; Rina Agutina; Bambang Sugiharto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research determines factors influence audit delays in manufacturing companies listed on Malaysian Stock Exchange for the period of 2019 until 2022. The model in this study consists of Profitability, Solvency, Company Size and Public Accounting Firm Size. Apart from that, this research also uses audit delay as a dependent variable. Secondary data used in this research are financial reports and audit reports from manufacturing companies listed on Malaysian Stock Exchange for the period of 2019 until 2022. The sample in this study consisted of 21 companies using purposive sampling techniques. The data analysis techniques used are descriptive statistics, classical assumption testing, and hypothesis testing using multiple linear regression analysis. The findings indicate that (1) Profitability has an effect on audit delay, (2) Solvency has no effect on audit delay. (3) Company size has no effect on audit delay. (4) Public Accounting Firm Size influences audit delay. (5) Simultaneously, Profitability, solvency, company size and Public Accounting Firm Size influence on audit delay.